AC MAGNETIC RESPONSE IN (Bi-2223+SrCO3)/Ag SUPERCONDUCTING TAPES - M. Diantoro‘; I. M. Sutjahja; M. O. Tjia; F. Gomory; P. Kovae (Jurnal Sains Materi Indonesia, 2002)
AC MAGNETIC RESPONSE IN (Bi-2223+SrCO3)/Ag SUPERCONDUCTING TAPES. A Bi-22231 Ag superconducting tape has been fabricated by means of conventional PIT, followed by eccentric and two axial rolling and heat treatment were introducing an oxide additive (SrCO3) as a barrier. Temperature dependent of AC magnetic susceptibility measurements have been conducted at various external ﬁeld Ba. The resulted data were analyzed on the basis of strip model using the wills bandfoiitizilation. It was found that the imaginary part ofthe critical current density at O K (Jco) is consistently larger than its real part, but both of them tend to decrease with increasing Ba.